Faktor Determinan yang Berhubungan dengan Partisipasi Masyarakat Usia ≥ 12 Tahun dalam Melakukan Vaksin COVID-19 - Syafrizal AR; Christin Angelina Febriani; Dessy Hermawan (LPPM Hang Tuah Pekanbaru, 2022)
One of the government's efforts in dealing with COVID-19 is with a self-limited disease-healing method. The way to do that is by implementing health protocols and carrying out special protection efforts, that as vaccination. This study aims to determine the determinant factors related to community participation aged 12 years old in carrying out the COVID-19 vaccine at Trimulyo Primary Health Center Work Area, Pesawaran Regency in 2022. This research is quantitative with a cross-sectional approach. The population in this study was people aged 12 years old in the Trimulyo Public Health Center, Pesawaran Regency, with 23,390 people. The sample was chosen with cluster random sampling, consisting of 394 people The data analysis used was univariate, bivariate (chi-square, and multivariate (multiple logistic regression). The results show that there was a relationship between knowledge (p = 0.033), history of non-communicable diseases (p = 0.004), history of COVID-19 (p = 0.005), and public perception (p = 0.000) with community participation in the COVID-19 vaccine. 19. The dominant factor related to community participation is the community perception variable. Suggested primary health care can intensify education to the community about the importance of carrying out the COVID-19 vaccine by using media which attracts more public attention.